Numerical study of natural ventilation in a building using CFD analysis - Lagumbay, Randy S. (The Mindanao Forum: official journal of the MSU-Iligan Institute of Technology, 2000)
A Computational Fluid Dynamics (CFD) analysis of the air temperature distribution, airflow pattern and particle tracks in a naturally ventilated building is conducted. The effect of changing the boundary condition to the air temperature field and air movement is studied. The commercial software like CFX 5.4.1 is used in the simulation and analysis of the physical model problem. Results show that changing the boundary condition will affect the air temperature distribution and air movement inside a building. The accuracy of the solution will depend on the accuracy of the wall boundary condition value.